Challenges faced by multinational companies in tax planning strategy using transfer pricing - Irbe, Jānis (Riga Graduate School of Law, 2024)
This work will identify ways in which MNE's use their privileges, from financial opportunities to influence, to use Transfer pricing (TP) as a way to reduce tax payments, establishing subsidiaries in specially selected countries. Within the framework of this work, the most important conditions for the preparation of documentation will be reviewed in order to gain a deeper understanding of the examples provided. Examining various examples, the emphasis will be placed directly on the use of Intellectual Property, so that profits can be successfully transferred to a lower tax zone. By using the intellectual property directly, the company does not need to hire a team of beach employees to the specific country, but to perform a significant part of the work remotely with a small number of employees.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Tax law; transfer pricing; tax planning; Multinational enterprise